Easy-to-prepare electrochemical platform composed of ionic liquid-Ni(II)-graphite composites: laboratory study on electrochemical oxidation of urea, alcohols, and glucose. (10th November 2015) - Chen, Jyun-Da; Lo, Nai-Chang; Huang, Genin Gary; Chen, Po-Yu
Graphical abstract: Highlights: An easy-to-prepare ionic liquid/Ni(II)/graphite composite has been developed. The electrode shows a behavior similar to those of Ni metal and Ni hydroxides. The coordination sphere of Ni(II) plays a crucial role on the electrode activity. The electrode shows good activity towards the oxidation of various compounds. Abstract: Ni(II) was introduced into four room-temperature ionic liquids (RTILs), namely 1-butyl-3-methylimidazolium salicylate (BMI-SAL), BMI hexafluorophosphate (BMI-PF6 ), 1-butyl-1-methylpyrrolidinium dicyanamide (BMP-DCA), and BMP bis((trifluoromethyl)sulfonyl) imide (BMP-TFSI), via the addition of NiCl2 or the anodic dissolution of Ni metal. The RTILs containing different Ni(II) species were mixed with pure and fine graphite (GP) powder to form RTIL/Ni(II)/GP composites, which were used to prepare composite electrodes for the electrocatalytic oxidation of urea, alcohols (methanol, ethanol, isopropanol, butanol, and glycerol), and glucose. Ni(II) produced from the anodic dissolution of Ni metal in BMP-TFSI showed the best activity. The BMP-TFSI/Ni(II)anodization /GP composite thus has potential as an easy-to-prepare electrochemical platform for the electrochemical oxidation of the above-mentioned compounds. The oxidation and determination of urea using the BMP-TFSI/Ni(II)anodization /GP composite electrode was thoroughly studied. A very high sensitivity of 517 μA·mM −1 ·cm −2 was obtained. This electrode also showed good stability during the anodic electrolysis of the aforementioned compounds, indicating that it may be appropriate as an anode for the electrolysis of urea, alcohols, and glucose.